Determinants of academics’ knowledge sharing behavior in United Arab Emirates Universities - Othman, Roslina; Skaik, Huda (International Foundation for Research and Development (IFDR), 2014)
This research aims to determine the factors affecting knowledge sharing behavior among academics in United Arab Emirates universities and identify the effect of university type on academics’ behavior. The research adopted Ajzen’s amended Theory of Planned Behavior. Employing an online survey, data were collected from academics in public and private universities using a questionnaire. The model was tested using Partial Least Squares structural equation modeling. The results found a significant difference in academics’ knowledge sharing behavior between public and private universities. Results also revealed that intention is the main determinant of knowledge sharing behavior, and that attitude, subjective norms, and self-efficacy have significant influence on intention while controllability has no influence on it. The significance of this research lies in that it is one of the first to use the amended theory and the only research to address knowledge sharing behavior in higher education in the Arab World. This research provides useful basis for higher education institutions to create a knowledge sharing culture and helps academics to enhance their performance.